THE USE OF PICTURES TO IMPROVE STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT AT GRADE VII OF MTs DDI KELURAHAN BARU TOLITOLI - Darwin, Darwin (Universitas Madako Tolitoli, 2017)
The objective of this research is to identify whether the use of pictures is effective to improve students’ skill in writing descriptive text. This pre-experimental study using 21 students as a sample. They are grade VIIB of MTs DDI Kel.Baru. The procedure of this research consisted of pretest, treatment, and posttest. The researcher give pretest and posttest to know the use of pictures can improve the students’ writing ability or not. The result of the analyse show that using pictures contribute greatly to the students in writing descriptive text. It can be see by the difference of the mean score between pre-test and post-test. The mean score of pre-test is 47.86 while in the post-test improved up to 80.10. The data of this research are analyse by using SPSS Program 16.0 Moreover the Minimum Mastery Criterion of English lesson was 75. Then the data of both tests are analyse by using T-test, and the result showed that the T-test value 15.505 is greater than T-table value 2.086. It can be inferred that use of pictures is very effective to improve students’ ability in writing descriptive text. Key words: Pictures, Improving, Writing, Descriptive Text.